Quincy's Market A Boston Landmark - Quincy, John Jr (Northeastern University Press, 2019)
A bustling commercial center and favorite tourist attraction on Boston's historic waterfront, Quincy Market, the popular name for Faneuil Hall Marketplace, draws throngs of visitors to the magnificent granite buildings and cobblestone concourses that house the area's specialty shops, restaurants, boutiques, pushcarts, and food stalls. Yet few are aware of the history of this legendary public place and its importance in the history of Boston and the nation. In this elegantly written and lavishly illustrated work, John Quincy, Jr., tells the absorbing story of the Market's unique evolution over the centuries. Beginning with John Winthrop's landing at the Great Cove on the Shawmut Peninsula in 1630, Quincy weaves together a remarkable tapestry of the district's rise, fall, and rebirth. Originally published by Northeastern University Press in 2003. With a new foreword by Hillary Corbett.